Vital Force and homœopathy - Hacker, C.F. (British Homeopathic Journal, 1948)
1. A connection is found between Hahnemann's conception of Vital Force and that of Cannon's “homœostasis”, which is maintained by the autonomic nervous system.2. Vital Force is traced to source in the embryo as it builds its body. It is seen laying down the “dynamic determination” on the multiplying tissue cells, and operating from the central mesodermal column, the notochord, to induct the Individuation Field of the elongating gastrula and differentiating neurula.3. A vital link between the notochord and the diencephalic centres isemphasized.4. The period of functional development sees the embryonic strugglebetween the autonomic system and the gene award. Such conflict is causative of defective autonomic balance, and the results have been noted by Hahnemann as the miasma, the psora, the sycoses.5. The thalamus, as the seat of sensory consciousness receiving both visceral and somatic sensory impulses transmits the sensory tone of the underlying autonomic fluster to the cerebral cortex for cognition. Such cognition is reported as symptoms, “I. …, My …”, thus giving the homœopathic picture of the “abnormally disturbed Vital Force”.6. The factors required in the blood's biochemical changes to maintain constant its pH level are given. The varying balance of the NaHCO3/H2CO3 content and Ca/K ratio may be related to Schuessler's “tissue remedies”.7. Such acid-base equilibrium is dependent on the autonomic functioning, which if impaired in the embryonic conflict is causative of allergy.8. Investigation of allergic factors produces an interesting formula ofhomœopathic significance, that shows the selected homœopathic remedy to be the catalyst key which declutches the autonomic imbalance.9. The varying bioelectric potential across the autonomic nerve gangliabetween diencephalic centres and fluid matrix brings about their functional activity and depression.10. A plea is made for a biochemical test of autonomic functioning.The autonomic nervous system is the meeting-ground of the homœopathicand allopathic divisions of medicine.If the disease process is acute or prolonged without permitting adequate intervals of functional rest to enable regrowth of its essential chromatin store, neurone degeneration follows. Such changes are not related to any specific bacterial action, but result from continuous functioning to exhaustion.The initial build-up of the autonomic path in reaction-response to externalstimuli is the essential basis of the individual's “modalities”.